GAMBARAN HISTOPATOLOGIK TESTIS MENCIT SWISS (Mus musculus) YANG DIBERI KEDELAI (Glycine max) DAN PAPARAN DENGAN ASAP ROKOK - Hargono, Felisia R. (e-Biomedik, 2013)
Abstract: Background: Cigarettes contain Polynuclear Aromatic Hydrogen and nicotine which can interfere with the process of spermatogenesis. The activity of free radicals can be inhibited by isoflavone and the amino acid arginine contained in soybean seeds.Objective: To reveal the histopathological features of the testis of Swiss rats exposed to cigarette smoke and administered with soybean. Method: Experimental research employed nine rats which were divided into three groups. Rats in Group A were fed with standard pellet for 35 days (negative control). Rats in Group B were exposed to cigarette smoke and were fed with standard pellet for 35 days. Rats in Group C were exposed to cigarette smoke and were fed with soybean 5 gr/day for 35 days. Results: Features of tubulus seminiferus with layers of spermatogenic cells which is in accordance with normal developmental stages were revealed in Group A. Meanwhile, in Group B, features of tubulus seminiferus with loose and irregular layers of spermatogenic cells were seen. Tubular lumen contained less spermatocytes and spermatid than Group A, making the lumen looked bigger and filled with less spermatozoa. In Group C, features of tubulus seminiferus with spematogenic cells which were denser than Group B were revealed. Conclusions: Exposure to the smoke of 2 cigarettes/day cause a decrease in the number of spermatogenic cells of the tubulus seminiferus in rat’s testis. The administration of soybean of 5 gr/day cause an increase in the number of spermatogenic cells of the tubulus seminiferus in rat’s testis exposed to cigarette smoke. Keywords: cigarette smoke, soybean, spermatogenic cell.   Abstrak: Latar Belakang: Rokok mengandung Polynuclear Aromatic Hydrogen dan nikotin yang dapat mengganggu proses spermatogenesis. Aktivitas radikal bebas dapat dihambat oleh isoflavon dan komponen asam amino arginin dalam biji kedelai. Tujuan: Untuk mengetahui gambaran histopatologis testis mencit swiss yang dipapar asap rokok dan diberikan kedelai. Metode: Penelitian eksperimental menggunakan 9 ekor mencit yang dibagi menjadi 3 kelompok. Kelompok A diberi pelet standar selama 35 hari (kontrol negatif). Kelompok B diberi perlakuan asap rokok dan pelet standar selama 35 hari. Kelompok C diberi perlakuan asap rokok dan makan pelet kedelai 5 gr/hari selama 35 hari. Hasil: Pada kelompok A didapatkan gambaran tubulus seminiferus dengan susunan lapisan sel spermatogenik sesuai tingkat perkembangan normal. Pada kelompok B didapatkan gambaran tubulus seminiferus dengan susunan sel spermatogenik yang longgar dan tidak teratur, lumen tubulus mengandung spermatosit dan spermatid yang lebih sedikit dibandingkan kelompok A sehingga lumen terlihat lebih besar dan tidak terisi penuh dengan spermatozoa. Pada kelompok C didapatkan gambaran tubulus seminiferus dengan sel spermatogenik yang lebih padat dibandingkan kelompok B. Simpulan: Pemaparan asap rokok 2 batang/hari menyebabkan berkurangnya jumlah sel-sel spermatogenik tubulus seminiferus testis mencit. Pemberian kedelai 5 gr/hari menambah jumlah sel-sel spermatogenik pada tubulus seminiferus testis mencit yang terpapar dengan asap rokok. Kata Kunci: Asap rokok, kedelai, sel spermatogenik.